2019
DOI: 10.1002/ecs2.2695
|View full text |Cite
|
Sign up to set email alerts
|

Use, selection, and home range properties: complex patterns of individual habitat utilization

Abstract: Individual patterns of habitat use emerge from behavioral decisions driven by interactions between landscape characteristics and individual traits. Individual traits, such as age and sex, influence the net gain of using habitats and associated resources, and thus the relationship between size and composition of the home range. However, the pathways from individual variation in home range size and composition to habitat selection are rarely fully explored. We investigated how habitat selection in moose (Alces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Males were more strongly tied to cropland than females. Sexdependent habitat selection is quite widespread within vertebrates and may be related to sex differences in offspring provisioning (Bergan and Smith, 1989;Laforge et al, 2021;Ofstad et al, 2019;van Toor et al, 2011). On the one hand, in Greek intensive agricultural landscapes, Vlachos et al (2015) reported that male lesser kestrels positively selected cereals and field margins while females preferred grasslands and cotton fields.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Males were more strongly tied to cropland than females. Sexdependent habitat selection is quite widespread within vertebrates and may be related to sex differences in offspring provisioning (Bergan and Smith, 1989;Laforge et al, 2021;Ofstad et al, 2019;van Toor et al, 2011). On the one hand, in Greek intensive agricultural landscapes, Vlachos et al (2015) reported that male lesser kestrels positively selected cereals and field margins while females preferred grasslands and cotton fields.…”
Section: Tablementioning
confidence: 99%
“…Additional factors that may contribute to explain inter-individual variability (but could not be considered in this study) include age/experience, personality, or body condition (e.g. Harris et al, 2020;Lesmerises and St-Laurent, 2017;Nilsen et al, 2009;Ofstad et al, 2019).…”
Section: Tablementioning
confidence: 99%
“…The average home range of females on high-risk sites doubled from the pre- to early-hunting seasons, but individual responses ranged from a 1052% decrease to a 98% increase. Perceived predation risk manifests individually [79,80], and responses are likely a complex process unique to each individual as trade-offs inherent in home range adjustments are likely sensitive to a range of factors including sex, age, experiences, body condition, resource availability, familiarity with the surrounding landscape [8184], and maybe most importantly, predator encounter rate [21]. Although there were substantial differences in the number of hunters between high- and low-risk sites (Fig 2), hunter movements within sites ultimately determine encounter rates for individual pheasants [85].…”
Section: Discussionmentioning
confidence: 99%
“…Moose are able to cross distances larger than the study area during the summer (Bjørneraas et al, 2010), making the entire island available. Consequently, habitat use is similar to habitat selection at the landscape scale, where habitat use is found to be proportional to availability, that is, no habitat selection (Ofstad et al, 2019). However, the high availability of open grassland implies that moose can frequently use this resource without necessarily showing a selection for it (Herfindal et al, 2009).…”
Section: Methodsmentioning
confidence: 99%